POLA KOMUNIKASI KEPEMIMPINAN NYAI DI PONDOK PESANTREN MODERN PUTRI LAMPUNG - Fitri Yanti (Indonesian Journal of Dialectics, 2011)
The research used the qualitative method through the case study of Nyai leadership in the Dinniyah Boarding School, Lampung. The results of the research show that: 1) The leadership strategy of Nyai consisted of : planning, cross- sector networking/cooperation, good relationship, socialization of boarding school, and visits to other boarding schools, 2) The function of Nyai communication involved giving information, getting relationship, conveying message, educating, changing attitude/behavior, persuading through Islamic preaching. 3) The leadership communication technique of Nyai consisted of : persuasive, dialogue, coercive, participative, and transcendental, 4) The communication pattern developed by Nyai was oral communication which tend to formal communication pattern and persistent to obidince or religion norms and The leadership communication model of Nyai in the boarding school was the discipline, autonomy, harmony, and relationship based leadership communication model as well as the conceptive and creative leadership of Nyai.